Waste polymers recycling in high performance asphalt mixtures - Silva, Hugo Manuel Ribeiro Dias da (2011)
Building a road pavement requires large amounts of constituent materials, whose extraction can lead to the devastation of natural resources and causes negative impacts on the environment. As aggregates comprise nearly 90% of asphalt mixtures, their partial substitution by waste thermosetting polymers (12 million tons of waste polymers are presently mislaid into landfills, every year, in Europe) can be considered as a sustainable technology, given that an equivalent performance can be assured. Thus, this study aims on evaluating possible advantages of introducing polyethylene based wastes in asphalt mixtures, namely high density polyethylene (HDPE) and cross-linked polyethylene (PEX), incorporating HDPE as a bitumen modifier and PEX as partial substitute of the aggregates. The laboratory tests carried out in this work showed that the use of HDPE significantly improves the behavior of the asphalt binder/mixture. The use of PEX considerably decreases the density of the mixtures, which can be attractive to lighten structures. The mixtures with PEX have similar performance to the conventional one in terms of water sensitivity, improving the permanent deformation resistance and reducing the temperature susceptibility. In brief, the mixtures incorporating waste polymers could be considered a good technical and environmental alternative for paving works.